Multiple behavioural risk factors and mental health among adults in Estonia - Opikova, Galina; Reile, Rainer; Konstabel, Kenn; Kask, Kristjan (Frontiers in Public Health, 2025)
AimExtensive evidence demonstrates the link between health behaviour and mental health. However, the impact of coinciding behavioural risk factors on mental health outcomes has received less attention. This study addresses this gap by analysing multiple behavioural risk factors and their association with mental health.Subject and methodsNationally representative data (n = 6,404) from 2020 cross-sectional survey in Estonia was used to examine patterns of co-occurring behavioural risk factors, including smoking, alcohol consumption, physical inactivity, unhealthy diet, drug use, and high screen time. Latent class analysis (LCA) was employed to identify behavioural classes, and binomial logistic regression was used to examine associations between predicted individual class membership and self-reported mental health outcomes, such as depressiveness, stress, suicidal thoughts, diagnoses of depression and insomnia, and medication use.ResultsLCA identified three behavioural classes: multiple risk factors (14.6%), low-risk lifestyle (79.9%), and drug use lifestyle (5.5%). Compared to individuals in the low-risk lifestyle class, respondents in the multiple risk factors and drug use classes had higher odds of experiencing depressiveness, stress, and suicidal thoughts, as well as self-reported diagnoses of depression and insomnia; they also exhibited increased use of medications, such as antidepressants, hypnotics, and sedatives.ConclusionBehavioural risk classes were associated with adverse mental health outcomes. These findings emphasise the importance of focused interventions targeting these risk factors to address the risk of mental health problems.